Sports-Based Tourism In Bone Bolango, Gorontalo - Mirdayani Pauweni; Tandiyo Rahayu; M.E Winarno; Heny Setyawati; Zainudin Amali (Universitas Negeri Semarang, 2021)
Development sport tourism in Gorontalo Province can be done by utilising sports-based tourism. Bone Bolango is one of districts that has the most tourist destinations in Gorontalo. This study aims to analyse the types of sports-based tourism in Bone Bolango. To achive the research objectives, a descriptive qualitative methode was used, applying observation and interviews with stake holders. The result of this study show that there are several of sports-based tourism in Bone Bolango Regency, such as swimming, snorkeling, diving, river tubbing, rafting, hiking and tracking, bike tracking, paragliding, trail adventure, offroad. This research can be used as reference material for further sport tourism research.